2016
DOI: 10.1088/1674-1056/25/2/020304
|View full text |Cite
|
Sign up to set email alerts
|

Mach–Zehnder interferometer with squeezed and EPR entangled optical fields

Abstract: We study a scheme for Mach–Zehnder (MZ) interferometer as a quantum linear device by injecting two-mode squeezed input states into two ports of interferometer. Two-mode squeezed states can be changed into two types of inputs for MZ interferometer: two squeezed states and Einstein–Podolsky–Rosen (EPR) entangled states. The interference patterns of the MZ interferometer vary periodically as the relative phase of the two arms of the interferometer is scanned, and are measured by the balanced homodyne detection sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The measurement of quantum noise is a vital step of many quantum optical experiments, such as squeezed state detection [1], coherent state detection [2], and quantum storage [3]. Balanced homodyne detection is a general method to measure quantum noise [4].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of quantum noise is a vital step of many quantum optical experiments, such as squeezed state detection [1], coherent state detection [2], and quantum storage [3]. Balanced homodyne detection is a general method to measure quantum noise [4].…”
Section: Introductionmentioning
confidence: 99%
“…Squeezed states are usually divided into two types: one is the bright squeezed state that has a coherent amplitude, and the other is the squeezed vacuum state that has no coherent amplitude. [1][2][3][4][5] Which type of squeezed light is desirable is dependent on the applications. In interferometer, the squeezed vacuum state is usually used to reduce the cross-interference influence due to no coherent amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Squeezed vacuum state, which is the brightest experimentally availble nonclassical light, has also received much attention. [9][10][11][12][13][14][15][16] In particular, it is found that an MZI with a two-mode squeezed vacuum state (TMSVS) and parity detection can offer sub-Heisenberg sensitivity. [10] In recent years, it is of particular interest to investigate the enhancement given by non-Gaussian states or operations for quantum communication, metrology, imaging, and information processing.…”
Section: Introductionmentioning
confidence: 99%